HETEROLOGOUS GENE EXPRESSION OF THERMOSTABLE LIPASE LK4 IN PICHIA PASTORISYEAST - Munawaroh, Laelia
Several isolated microorganism s from compost are well known for having a good lipase activity. Lipase is an enzyme that has broad applications in various industrial biotechnology processes, for example in the food industr y, specially in the making process of cheese or chocolate; in the pharmaceutical industry as enantioselective directors in the manufacture of drugs from a racemic; and in the biodiesel industry as a catalyst for transesterification reactions. The high potent ial of lipase as a biocatalyst in vari ous industrial processes encourages the development of various new studi es to increase lipase prod uction. Particular strategy to thi s challenge is by utilizing the recombinant DNA technology. Recombinant DNA technology is a series of biotechnological processes that make it possible to modi fy genes, isolate genes, and express genes in other organisms.